Memo from Trudy Owens and letter from Jesse M. Unruh - Jesse M. Unruh::::::; Trudy Owens:::::: (1964)
This document contains two pieces of correspondence related to Democratic Party activities in 1964. The first, a November 12, 1964 memo from Trudy Owens of the Democratic State Central Committee, asks Southern California nominees to submit names of outstanding women volunteers to be honored at a January Key Awards Brunch, particularly those active in registration and get-out-the-vote efforts. She notes that Speaker Jesse M. Unruh will present the awards. The second, dated July 9, 1964, is a letter from Jesse M. Unruh congratulating Jane Tolmach on her election to the Democratic County Central Committee. Unruh emphasizes strengthening the committee's role and urges unity and hard work to secure Democratic victories in the November election.